2021
DOI: 10.3390/ma14113064
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Impact Assessment of Load-Bearing Straw Bale Residential Building

Abstract: As a renewable raw material, straw bale represents a sustainable way of construction with minimal environmental impact. This paper focused on life cycle impact assessment of load-bearing straw bale residential building. Product stage from raw materials extraction to manufacture of construction materials was considered in the assessment including seven variations of straw bale. Construction materials were evaluated due to IMPACT 2002+ method. Both midpoint and endpoint impact categories were included. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…However, introducing abiotic insulation material lowered carbon removals, resulting in an overall carbon balance of almost 3% compared to the LDF alternative. Therefore, it can be concluded that natural-based construction materials might not be a sustainable solution that complies with the findings of other authors [31,32]. However, future studies might be focused on the application of bark-based panel insulation [33].…”
Section: Discussionsupporting
confidence: 76%
“…However, introducing abiotic insulation material lowered carbon removals, resulting in an overall carbon balance of almost 3% compared to the LDF alternative. Therefore, it can be concluded that natural-based construction materials might not be a sustainable solution that complies with the findings of other authors [31,32]. However, future studies might be focused on the application of bark-based panel insulation [33].…”
Section: Discussionsupporting
confidence: 76%
“…Current insulation materials such as polystyrene, polyisocyanurate, and PUR foams in the construction market are generally based on fossil resources with a great insulation performance but with high environmental impact due to their production processes [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of sustainable and recyclable materials is an important aspect to warrant a healthy environment. Many studies scrutinized the environmental and technical benefits of using sustainable materials (natural or recycled) as basic elements to produce commonly used as well as new porous materials (granular or fibrous) [11][12][13][14][15][16][17][18] such as rice husk, cotton stalk, jute fiber, straws of wheat, hemp, flax, coconut fibers, stalks of maize and sheep's wool [19][20][21][22][23][24][25]. These lignocellulosic materials, when used appropriately, can provide thermal and acoustic insulation performance comparable with the most used insulation materials, but with excellent environmental properties [26].…”
Section: Introductionmentioning
confidence: 99%